2012
DOI: 10.1002/mus.23656
|View full text |Cite
|
Sign up to set email alerts
|

Falls and spinal muscular atrophy: Exploring cause and prevention

Abstract: Stride-length variability was the key variable associated with falls. Preventive strategies to avoid falls should be incorporated into patient management plans. Gait analysis provides actionable information not revealed by standard assessments and should be included in clinical trials designed to address the prevention of falls in the SMA population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…The average stride-length variability obtained in this study was in line with the estimates obtained in our previous work, which showed an association between this gait parameter and a history of falls in patients with SMA. 24 Consistent with previous reports, 3,4 we found decreasing stride length to contribute most to fatigue-related changes in speed. Moreover, we found that SMA patients walk predominantly on their forefoot with a reduced initial heel strike, and the foot-flat phase occurs early in the gait cycle.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The average stride-length variability obtained in this study was in line with the estimates obtained in our previous work, which showed an association between this gait parameter and a history of falls in patients with SMA. 24 Consistent with previous reports, 3,4 we found decreasing stride length to contribute most to fatigue-related changes in speed. Moreover, we found that SMA patients walk predominantly on their forefoot with a reduced initial heel strike, and the foot-flat phase occurs early in the gait cycle.…”
Section: Discussionsupporting
confidence: 92%
“…Unlike instrumented walkways, instrumented shoes allow us to easily record hundreds of footfalls in a single session (e.g., during the 6MWT, a well‐established mobility test). The average stride‐length variability obtained in this study was in line with the estimates obtained in our previous work, which showed an association between this gait parameter and a history of falls in patients with SMA …”
Section: Discussionsupporting
confidence: 91%
“…Slower gait speed correlated with increased falls as previously demonstrated in older adults,28 however was a weaker predictor than age and balance in children with CMT. BOS variability was increased in the CMT group compared with TD peers and associated with reduced balance in this group,19 similar to other neurological populations 11 29. Failure to detect a significant association in this study may be due to the small sample size and heterogeneity within the CMT cohort.…”
Section: Discussionmentioning
confidence: 53%
“…Scoliosis is almost inevitable, requiring surgical intervention to support the spine. In patients with mild SMA, falls and fractures associated with fatigue and gait abnormalities are commonly reported and require the incorporation of preventive strategies into patient management plans [85]. Efforts to more directly address the cause of SMA-low SMN-mostly focused on histone deacetylase (HDAC) inhibitors, a class of compounds known to have a general effect on the expression of subset of genes [86].…”
Section: Current Optionsmentioning
confidence: 99%